Mortalitas wereng batang cokelat (Nilaparvata lugens Stal) asal Karawang terhadap bahan aktif insektisida triflumezopyrim dan buprofezin - Arfah Fadmajani; Muhammad Zainal Fanani; Oktavianus Lumban Tobing; Budi Irfan (JURNAL AGRONIDA, 2025)
This study was aimed to determine the mortality of brown planthoppers (Nilaparvata lugens Stal) from several sub-districts in Karawang to the active ingredients of the insecticides triflumezopyrim and buprofezin. This study was carried out from March 2025 to May 2025 in Lemahabang District, Karawang Regency. This study used N. lugens test samples from standard populations and field populations (populations from three sub-districts). The testing method used was the dipping method in accordance with IRAC method number 005. This study employs a completely randomized design with 9 treatments and 3 replications including Control (I0), Triflumezopyrim 0.4 mL/L (I1), Triflumezopyrim 0.8 mL/L (I2), Triflumezopyrim 1.6 mL/L (I3), Triflumezopyrim 3.2 mL/L (I4), Buprofezin 1.25 mL/L (I5), Buprofezin 2.5 mL/L (I6), Buprofezin 5 mL/L (I7), and Buprofezin 7.5 mL/L (I8). The Duncan Multiple Range Test at the 5% level was used to analyze the data after the analysis of variance, conducted if the results showed significant differences. The research results show that the insecticide with the active ingredient triflumezopyrim is effective in causing mortality in N. lugens across all test populations, both from standard and field populations, with a mortality rate up to100% at a concentration of 0.8 mL/L.